Microbiological characteristics of meliponine honey marketed in the State of Paraná – Brazil (Research, Society and Development, 2021)
Meliponine is a honey with particular characteristics; it has a high percentage of humidity, which can favor the development of microorganisms, thereby causing changes in the quality of the product. The objective of this study was to evaluate the microbiological characteristics of meliponine honey produced by different species and marketed in the State of Paraná-Brazil. The sample unit was composed of honey of Tetragonisca angustula (n = 15), Scaptotrigona bipunctata (n = 05), Melipona quadrifasciata quadrifasciata (n = 05) and Melipona bicolor schencki (n = 01). The following microbiological parameters were evaluated: counts of total and thermotolerant coliforms, fungi count and detection of Salmonella spp. Principal component analysis (PCA) was used to evaluate the possible relationships among species, locality and type of microorganism. For microorganisms of the total coliform group, 15.38% of the analyzed samples had values >3 MPN/g. The presence of thermotolerant coliforms was observed in 7.69% of the samples, all of which were T. angustula samples. For fungi counts, 100.00% of the analyzed samples had values within the established range created by the Agricultural Defense Agency of Paraná. The presence of Salmonella spp. was not observed in any of the samples evaluated. The amount of water in the honey is related to the location of the apiary and edaphoclimatic factors. Adoption of good handling practices by beekeepers is indispensable for the safety of the final product.